Work-related ill-health in radiographers. (17th May 2018) - Hulls, P M; Money, A; Agius, R M; de Vocht, F
Abstract: Background: In the UK in 2015/16, 1.3 million workers self-reported a work-related illness (WRI) of which an estimated 41% were due to musculoskeletal disorders (incidence rate 550 cases per 100000 people) and 37% were related to stress, anxiety and depression. Little is known about the incidence of WRIs in radiographers. Aims: To analyse the medically reported incidence of WRIs among radiographers in the UK between 1989 and 2015. Methods: Incident cases reported by physicians to The Health and Occupation Research (THOR) network through its specialist schemes from 1989 to 2015 were analysed, using the Labour Force Survey as denominator where appropriate. Results: In total, 218 cases (966 estimated cases) were reported. Of these 190 were in women. The mean age was 40.2 (20–91 years) SD ± 11.8 years. Most cases were reported to the Occupational Physicians Reporting Activity (OPRA) scheme ( n = 92). A skin diagnosis was the most frequently reported ( n = 77), followed by musculoskeletal ( n = 60). Within the EPIDERM scheme, radiographers had the highest incidence rate when compared to all other occupations. Conclusions: Radiographers had a higher incidence of WRI compared to all other occupations. The most frequently reported WRI was skin conditions. The observed increase in incidence is likely to be due to the increase in the number of radiographers over that time period, although there was no evidence that WRI within radiographers are declining.